Al Mawaddah In The Quran (A Thematic Interpretation Perspective) - Darmawan, Agus; Mustofa, Ali; Mollah, Moch. Kalam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This writing discusses the interpretation of al-mawaddah from the perspective of the Qur'an. The aim of this research is to understand how al-mawaddah is interpreted from the perspective of the Qur'an. To obtain data, the author conducted data collection through a literature study to understand the concepts of interpreting the term from the perspective of the Qur'an. From the data analysis conducted, the author found that al-mawaddah can be interpreted as